The Resolution and Sensitivity Function of Electrode Arrays in 2D Resistivity Imaging Technique - Al-Zubedi , Ahmed; Abdulrazzaq, Zaidoon (Malaysian Journal of Science, 2025)
Two synthetic models are employed to assess the relationship between resolution and sensitivity function of electrode arrays: Dipole-Dipole, Pole-Dipole, Wenner-Schlumberger, and Wenner arrays. Both models were designed with a survey line length of 100 m and minimum electrode spacing of 0.5 m. Each model includes two rectangular structures measuring 3 meters in length and 2 meters in width, positioned at depths from 4.44 meters to 6.44 meters. These structures are separated by 3 meters and 6 meters, respectively. After generating over 20 inverse models, the results indicated that electrode array resolution is not related to the sensitivity function but depends on the separation distance between subsurface structures rather than electrode spacing. Additionally, increased data coverage does not correlate with resolution, as higher measurement density failed to differentiate between separate structures. These factors cannot be considered significant or influential in developing a high-resolution model. Therefore, we recommend combining other geophysical methods with this technique when investigating subsurface structures separated by small distances.